Environmental impact assessment of rice production in Indonesia: A case study from Jatibarang, West Java - Indah Permata Sari; Ika Wahyu Utami; Dian Mardi Safitri; Sucipto Adisuwiryo; Ahmad Farhan (Songklanakarin Journal of Science and Technology (SJST))
The agricultural sector is one of the contributors to global warming, for example by rice cultivation that produces the greenhouse gases methane and carbon dioxide. This study aims to assess the environmental performance of rice production in Jatibarang District, Indramayu Regency, West Java Province, as one of the largest rice producers in Indonesia. The method used in this study is life cycle assessment, highlighting the rice production stage with the most significant impact. SimaPro 9.2.0 software and the Recipe 2016 Midpoint method were used to determine the environmental impact of rice production. A total of 18 environmental impacts of rice production were assessed, and the analysis focused on the effects on global warming, acidification, and eutrophication. The impact assessment resulted in a value of 734 kg CO2 eq for global warming, 3.13 kg SO2 eq for terrestrial acidification, and 0.228 kg P eq for freshwater eutrophication. The hotspot analysis shows that using chemical fertilizers in the form of urea and NPK gave the most significant contribution to the overall impact evaluated. The application of LCA in the agricultural sector can provide information to help policymakers understand the potential environmental impacts of rice production at various spatial scales.